2019
DOI: 10.1161/jaha.119.013249
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality and Cardiovascular Disease Risk in Postmenopausal Women With Type 2 Diabetes Mellitus: The Women's Health Initiative

Abstract: BackgroundDietary patterns are associated with cardiovascular disease (CVD) risk in the general population, but diet–CVD association in populations with diabetes mellitus is limited. Our objective was to examine the association between diet quality and CVD risk in a population with type 2 diabetes mellitus.Methods and ResultsWe analyzed prospective data from 5809 women with prevalent type 2 diabetes mellitus at baseline from the Women's Health Initiative. Diet quality was defined using alternate Mediterranean,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…The Paleolithic diet consists of the intake of proteins (e.g., lean meat, fish, and eggs) and food from uncultivated plant sources, and excludes food unavailable before humans started to cultivate plants such as dairy products, grains, legumes, salt, refined sugar, and processed oils. Although no association was observed in postmenopausal women with T2DM between the paleolithic score and the risk of CVD [30], most studies concluded that this diet has benefits for patients with diabetes and an increased cardiovascular risk [208]. In this respect, the paleolithic diet has proved to lower BMI, CRP levels, and systolic and diastolic blood pressure [209] as well as myocardial triglyceride levels [210] and all-cause and cause-specific mortality [211], while improving left ventricle remodeling [208], leptin levels, insulin sensitivity, and glycemic control [212,213].…”
Section: Dietary Patterns For the Management Of Patients With Cvd And Dmmentioning
confidence: 88%
See 1 more Smart Citation
“…The Paleolithic diet consists of the intake of proteins (e.g., lean meat, fish, and eggs) and food from uncultivated plant sources, and excludes food unavailable before humans started to cultivate plants such as dairy products, grains, legumes, salt, refined sugar, and processed oils. Although no association was observed in postmenopausal women with T2DM between the paleolithic score and the risk of CVD [30], most studies concluded that this diet has benefits for patients with diabetes and an increased cardiovascular risk [208]. In this respect, the paleolithic diet has proved to lower BMI, CRP levels, and systolic and diastolic blood pressure [209] as well as myocardial triglyceride levels [210] and all-cause and cause-specific mortality [211], while improving left ventricle remodeling [208], leptin levels, insulin sensitivity, and glycemic control [212,213].…”
Section: Dietary Patterns For the Management Of Patients With Cvd And Dmmentioning
confidence: 88%
“…The current situation of cardiometabolic patients could probably be improved or even reversed by nutritional intervention, which consists of an adequate nutrition by adapting dietary patterns and reducing calorie intake [24] as it has been successfully proven in some conditions such as cancer [25], neurodegenerative diseases [26], or heart failure [27]. However, the role of nutritional intervention in patients with CVD and T2DM is scant [28][29][30][31] and should be well-described and updated from time to time since it would allow learning to identify each food group correctly as well as establishing better diets as a fundamental part of the treatment for those patients. For these reasons, and due to the link that obesity has with multiple metabolic dysfunctions that increase the risk of CVD, the aim of this review was to examine the importance of nutrition in patients with both type 2 diabetes mellitus (T2DM) and CVD.…”
Section: Introductionmentioning
confidence: 99%
“…In the Nurses' Health Study, the highest AMED quintile had lower risk of CHD (RR 0.71, 95% CI 0.62-0.82), fatal CHD (RR 0.58, 95% CI 0.45-0.75), and non-fatal CHD (RR 0.78, 95% CI 0.66-0.93) compared to the lowest quintile. Similar reductions in the risk of CVD (HR 0.77, 95% CI 0.65-0.93), CHD (HR 0.69, 95% CI 0.53-0.91), and stroke (HR 0.67, 0.0.47-0.96) were observed in a prospective analysis of women with type 2 diabetes participating in the Women's Health Initiative when the highest diet quality assessed by the AMED (quintile 5) was compared with the lowest diet quality (quintile 1) [23]. A number of other Mediterranean-diet-based indices have been developed that are used in research [24].…”
Section: Indices Based On Foods or Dietary Patterns Associated With Risk Of Chronic Diseasementioning
confidence: 99%
“…Similarly, higher intake of fruits, vegetables, high unsaturated-to-saturated fat ratio, which were reflected in the DASH and Mediterranean diet and evaluated by AHEI-P, was associated with a lower risk of NCDs [29,30]. Interaction of these food components would provide a better sodium-to-potassium ratio affecting plasma renin activity and lead to an increase of sodium excretion by the kidneys [31].…”
Section: Plos Onementioning
confidence: 99%